Rezension von: Bayer, Hans Joachim; Schuster, Gerhard, Besucherbergwerk "Tiefer Stollen" - Bienert, Hans-Dieter (Württembergisch Franken, 1989)
Hans Joachim Bayer; Gerhard Schuster: Besucherbergwerk »Tiefer Stollen«. Erzbergbau in Aalen-Wasseralfingen. Stuttgart: Theiss 1988. 169 S., 132 Abb.